Listful thinking : using lists to be more productive, highly successful and less stressed - Rizzo, Paula (New York : Viva Editions, 2014)
'If you're part of the [37% of people who don't make to-do lists] and feel like you're chasing your own tail I've got news for you: it doesn't have to be that way. You can still find time to relax, read a good book, and do the things you love. Listful Thinking is the book that will give you your life back. It will show you how to save time, be more organized, be more productive, save money, and reduce stress'--
Keywords: Motivation (Psychology).; Time management; Stress management; Success; Achievement; Motivation; Stress, Psychological -- prevention & control; Time Management